Pharmacokinetics of Isavuconazole During Extracorporeal Membrane Oxygenation Support in Critically Ill Patients: A Case Series - Laura Doménech-Moral; Sonia García-García; Alba Pau-Parra; Manuel Sosa; Adrian Puertas Sanjuan; Camilo Bonilla; Elisabeth Gallart; Laura Castellote; Patricia Faixó; Jessica Guevara; Albert Vilanova; María Martínez-Pla; et al. (Antibiotics, 2025)
Background/Objectives: Extracorporeal membrane oxygenation (ECMO) is increasingly used in critically ill patients, but may significantly alter the pharmacokinetics (PK) of antifungals. Data on plasma concentrations of Isavuconazole (IsaPlasm) in ECMO patients are limited. Our objective is to evaluate Isavuconazole exposure and variability in critically ill COVID-19 patients receiving ECMO. Methods: We conducted a pharmacokinetic analysis of Isavuconazole in critically ill patients receiving Veno-Venous ECMO for respiratory support. Plasma concentrations were measured using therapeutic drug monitoring (TDM) at multiple time points, including sampling before and after the membrane oxygenator. PK parameters—Area Under Curve (AUC0–24), Minimum Plasma Concentration (Cmin), Elimination Half-Life (T1/2), volume of distribution (Vd), and clearance (CL)—were estimated and compared with published data in non-ECMO populations. Results: Five patients were included. The median AUC0–24 was 227.3 µg·h/mL (IQR 182.4–311.35), higher than reported in non-ECMO patients. The median Vd was 761 L (727–832), suggesting extensive peripheral distribution and potential drug sequestration in the ECMO circuit. CL was increased (1.6 L/h, IQR 1.5–3.4). Two patients with recently replaced ECMO circuits exhibited significant drug loss across the membrane. Obesity and hypoalbuminemia were identified as factors associated with altered drug exposure. Conclusions: Isavuconazole pharmacokinetics show marked variability in critically ill ECMO patients. Increased AUC and Vd, along with reduced clearance, highlight the need for individualized dosing.